Conventionality control and international judicial supremacy - Orunesu, Claudina (Revus (Ljubljana), 2020)
According to the American Convention on Human Rights, the Inter-American Court is the competent body to "comprise all cases concerning the interpretation and application of the provisions of the Convention that are submitted to it". In this normative framework, in 2006 the Inter-American Court introduced the so-called conventionality control doctrine. In doing so, it has not restricted itself to maintaining that municipal judges must control the compatibility of domestic laws with the text of the American Convention, but claimed that they must also take into account the interpretation thereof made by the Inter-American Court, which is the ultimate interpreter of the American Convention". This view of conventionality control, that also involves a particularly strong notion of international judicial supremacy, constitutes a consolidated doctrine of the international tribunal. However, certain objections seem to be arising around the doctrine and the particular style with which the Inter-American Court exercises it. This paper aims to show that the basis of the doctrine of conventionality control in its current configuration, i.e., the supremacy of both conventional law and the interpretative criteria fixed by the Inter-American Court, may lead to paradoxical consequences and raises doubts concerning the role the Inter-American Court plays today in the adjudication process regarding the Convention. Finally, considering a recent challenging decision of Argentina`s Supreme Court, some reformulations of the conventionality control doctrine will be explored.
Keywords: conventionality control; Inter-American Court of Human Rights; judicial dialogue; judicial supremacy; konvencijski nadzor; legal interpretation; Medameriško sodišče za človekove pravice; pravno razlaganje; sodniški dialog; vrhovnost pravosodja